Qualitative disaster research - Phillips, Brenda D. (Understanding qualitative research, 2014)
"Research that occurs in the context of emergencies and disasters requires attention to challenging contexts and circumstances. Qualitative Disaster Research walks readers through the ways in which those contexts can be managed to produce careful, rigorous, and scholarly work. Each chapter provides an overview of approaches, methods, and techniques with illustrations from established disaster studies. Step-by-step instructions outline ways to gather, analyze, and write up qualitative field data. User-friendly examples show readers how to move from initial research ideas to final publication. Throughout the volume, readers find helpful suggestions for a range of field-based scenarios. Qualitative Disaster Research stands out of the first volume of its kind with the singular intent to serve as a guide to those new to or wanting a refresher course in disaster studies. Students and faculty will find the book approachable and ideal for use in training the next generation of disaster researchers"..